Analysis of Factors that led to Financial Crisis in 2007 within the Context of Efficiency Market Hypothesis - Kredatus, Kristián (2018)
The goal of this thesis is to determine what role the Federal Reserve, the U.S. regulatory framework as a whole and the global imbalances played in the forming of the financial crisis of 2007. The thesis addresses numerous popular misconceptions of the causes and tries to separate the correct criticism from the faulty ones. The whole topic is put within the context of the Efficient Market Hypothesis (EMH), which has been shaping the ideology of many people from the field of finance and economics, mainly during the 20th century. The work then analyzes whether the ideology of EMH was implemented into the regulatory and economics framework and helped to build-up the crisis.